Shifts in the demographics and behavior of bearded pigs (Sus barbatus) across a land-use gradient - Davison,CW; Chapman,PM; Wearn,OR; Bernard,H; Ewers,RM (Biotropica, 2019)
Beyond broadscale investigations of species diversity and abundance, there is little information on how land conversion in the tropics is affecting the behavior and demographics of surviving species. To fill these knowledge gaps, we explored the effects of landuse change on the ecologically important and threatened bearded pig (Sus barbatus) over seven years in Borneo. Random placement of camera traps across a landuse gradient of primary forest, logged forest, and oil palm plantations (32,542 trap nights) resulted in 2,303 independent capture events. Landuse was associated with changes in the age structure and activity patterns of photographed individuals, alongside large changes in abundance shown previously. The proportion of adults recorded declined from 92% in primary forests to 76% in logged forests, and 67% in plantations, likely indicating increased fecundity in secondary forests. Activity level (capture rate) did not vary, but activity patterns changed markedly, from diurnal in primary forests, crepuscular in logged forests, to nocturnal in plantations. These changes corresponded with avoidance of diurnal human activity and may also protect bearded pigs from increased thermal stress in warmer degraded forests. The percentage of adult captures that were groups rather than individuals increased fivefold from primary forests (4%) to logged forests (20%), possibly due to increased mating or in response to perceived threats from indirect human disturbance. We recommend further investigation of the demographic and behavioral effects of landuse change on keystone species as altered population structure, activity patterns, and social behavior may have knockon effects for entire ecosystems.